Emerging role of robotics in urology - Kumar Rajeev; Hemal Ashok (Journal of Minimal Access Surgery, 2005)
Robotic assistance is one of the latest additions to the field of laparoscopic surgery. The most commonly used robotic device in Urology is the da Vinci ® system of which over 200 devices are installed worldwide including 3 in India. This robot consists of three or four arms, one of which is used to hold and manipulate the laparoscopic camera while the others are used to manipulate specialized laparoscopic instruments with endowrist ® technology that allows 7 degrees of freedom. The robot is currently used primarily for radical prostatectomies where complex dissection and reconstruction can be performed in less than 2 hours with excellent outcomes. There is a progressive increase in the number of surgeries being performed by this device which allows laparoscopy naοve surgeons to offer the benefits of minimally invasive surgery to their patients. The other surgeries where this device has been used to benefit are pyeloplasty, cystectomy with urinary diversion, nephrectomy and ureteric re-implant. The principal drawbacks of the device are the steep cost of machine and disposables. However, the benefits achieved in terms of improved surgical precision, magnified 3 dimensional vision, scaling of movements, remote surgery and as a teaching tools will help the robot establish a definitive place in the urologic armamentarium.